Structural and productivity changes from introducing strong user rights in the Danish demersal fisheries. (January 2023) - Nielsen, Rasmus; Hoff, Ayoe; Andersen, Jesper L.
Abstract: This study examines structural and total factor productivity changes given the transition to a management system introducing stronger user rights (SURs) embedded in an individual transferable quota (ITQ) management scheme for the Danish demersal fishery in 2007. The focus is on the four most profitable Danish demersal segments. A Malmquist index approach is applied over the 2000–2016 period, thus capturing possible changes before and after the management change. This is supplemented by a quantitative analysis of the structural changes in fleet capacity and catches over the period. The analyses first show that total factor productivity (TFP) decreased from 2000 to 2006 and increased after the introduction of stronger user rights from 2007 to 2016 for all segments. Segments with access to the North Sea experienced higher productivity growth than segment fishing in the Baltic Sea. Some segments experienced high productivity growth in the year just before the change and an influx of vessels, which is believed to have been caused by the strategic behaviour of the fishers. The overall conclusion is that introducing strong user rights has had a positive effect on TFP growth and has further led to corresponding capacity reduction in the Danish demersal fisheries.